1997
DOI: 10.1016/s1350-4177(96)00016-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of frequency on sonochemical reactions III: dissociation of carbon disulfide

Abstract: Investigations were made of the effects of frequency, temperature, intensity and gases on the rate of sonochemical dissociation of carbon disulfide. Application of 900 kHz ultrasound did not produce any noticeable change. When carbon disulfide was irradiated with 20 kHz, the liquid formed a heterogeneous mixture of black particles in a yellow solution. The rate of dissociation decreased with increasing temperature, in agreement with most sonochemical reactions. The rate also decreased with decreasing area of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 6 publications
2
42
0
Order By: Relevance
“…This is the reason with highly efficient degradation in the presence of these gases. In addition to this, the solubility of gas possesses a role in the degradation, and the order is found to be He (Entezari et al 1997), and thus, the enhancement of the cavitational event is in the same order. Similarly as the thermal conductivity of dissolved gas increases, the amount of heat loss due to thermal dissipation also increases.…”
Section: Sonochemical Degradation Of Pharmaceutically Active Compoundsmentioning
confidence: 93%
“…This is the reason with highly efficient degradation in the presence of these gases. In addition to this, the solubility of gas possesses a role in the degradation, and the order is found to be He (Entezari et al 1997), and thus, the enhancement of the cavitational event is in the same order. Similarly as the thermal conductivity of dissolved gas increases, the amount of heat loss due to thermal dissipation also increases.…”
Section: Sonochemical Degradation Of Pharmaceutically Active Compoundsmentioning
confidence: 93%
“…In the past, typical sonochemical reactions were carried out at frequencies between 20 and 50 kHz. la some reactions, alteration of frequency has no apparent effect, sudi as the in the dissociation of carbon disulfide (Entezari et al, 1997). However, in other reactions, such as oxidations, current research is finding that higher frequencies may lead to higher reaction rates.…”
Section: G Ultrasonic Frequencymentioning
confidence: 98%
“…The dependence of cavitational intensity on the characteristics of the dissolved gases has been studied by Entezari et al (1997) vsdio investigated the effect of ultrasound on the rate of carbon disulfide dissociation. Th^ found that He gave the hi^est reaction rate and CO2 gave the lowest, with the rate decreasing in the following ordra^ of gases present: He > H2 > air > Ar > O2 > C02-Since argon has a hi^er ^edfic heat ratio that helium, th^ were piuzled with the observations.…”
Section: A Presence Of Dissolved Gasesmentioning
confidence: 99%
See 2 more Smart Citations